Reading Note 3: Categories and roles of stakeholders in living landscapes - Navarrete-Cruz, Angela; Triomphe, Bernard; Nehring, Ryan; Bergamini, Nadia (2024)
This Note is the third of a series of reading notes reviewing selected literature on concepts, approaches, methods, and experiences that the Initiative on Agroecology (IAE) and particularly its WP1 employs for the emergence and consolidation of Agroecological Living Landscapes (ALLs) aimed at fostering agroecological transitions. The Note focuses on the categories and roles of stakeholders. As actor-based processes, ALLs rely on the capacity and willingness of stakeholders to play certain roles and fulfill responsibilities to achieve established goals. Recognizing stakeholder categories is an important process in LLs, as categories point out grosso modo who and who will not be included. This is a political decision that could ultimately determine who is empowered through LLs and who is not. Identifying roles, for its part, influences how stakeholders are empowered (or not), how they could mobilize their “pre-existing” power, and in general, how ALLs influence the power balances among different stakeholders.